Sustainable development framework of historical cities. A case study: city of Soltaniyeh.Iran - Ojaghlou, Morteza (Journal of Architecture and Urbanism, 2020)
Unfortunately, the architecture and urbanization of the Iranian cities, especially the traditional Iranian cities in the present era, are in many cases in contrast to the historical, social, and cultural background of these cities. In this study, architectural design in small historical cities such as Soltaniyeh has been explored to achieve a conceptual and sustainable architecture through a research-based library approach inference. Achieving the principles of architectural design in the historic city of Soltaniyeh. Iran is the main concern of this research. Therefore, to reach an integrated design process, previous studies and projects were examined and analyzed and the obtained data and principles, including historical, cultural, social, natural, climate, were in the design process of the real project. As a final result of this study, the integrated design process of these parameters is presented as a process of architectural design in small historical cities such as Soltaniyeh.